Economic Sanctions: Astute Policy or Just another Barrier to Free Trade? - Rarick , Charles A. (American Journal of Trade and Policy, 2016)
When mentioning free trade the topic of economic sanctions is seldom mentioned. However, governments of the developed world, especially the United States, have used economic sanctions as a foreign policy tool to compel other countries to change their behavior. The increasing use of economic sanctions as a form of foreign policy is not without cost, however, and that cost is borne by citizens of sanctioned countries and businesses who find international markets closed to them, either entirely or in part. In addition, consumers pay a price through less choice and higher prices. Economic sanctions are barriers to free trade and interfere with the free flow of goods and services. This case examines the current state of economic sanctions imposed by the United States and explores sanctions imposed on Cuba, Myanmar and Iran; three heavily sanctioned countries which recently have experienced a change in U.S. foreign policy action, yet still suffer from trade restrictions.
Keywords: economic sanctions; non-tariff barriers; trade theory